(untitled) (Asian Education Studies, 2018)
Learning using 1:1 mobile devices is a partnership between the user and the curriculum, where learning interventions are strategically integrated to foster critical thinking skills for effective problem solving. The purpose of this research study is to explore the question. How can 1:1 mobile technology be used to develop critical thinking skills and support creativity? The skill of problem solving is evidence of applied critical thinking during targeted learning. The literature review and focus group results, contextualise and aim to demonstrate how learners are using 1:1 mobile devices to develop critical thinking skills to achieve problem solving outcomes. Engineering courses that are using problem orientated design-based learning and are allowing students to use 1:1 mobile devices, need to support students by including targeted learning interventions. Learning interventions using active learning (self-directed learning) principles that are designed to teach critical thinking skills to achieve higher order problem solving outcomes for ‘real world’ solutions. Focus group results are included in this research study to highlight students’ perceptions when using 1:1 mobile devices for learning as evidence of applied critical thinking skills.